Personality Counts More Than Appearance for Men Making Affective Judgments of Verbal Comments - Gao, Shan; Luo, Lizhu; Zhang, Wanyu; Lan, Yuxin; Gou, Ting; Li, Xun (Frontiers in Psychology, 2019)
Previous research has shown that that evaluative verbal information (praise and criticism) conveys different affective values: criticism is perceived as unpleasant while praise is generally considered pleasant. Here, using praise and criticism in Chinese, we investigated how affective value is modulated in men and women, depending on the particular attribute (personality vs. appearance) targeted by social comments. Results showed that whereas praise was rated as pleasant and criticism as unpleasant overall, criticizing personality reduced pleasantness more than criticizing appearance. In men, moreover, criticism of personality was deemed more unpleasant than criticism of appearance while personality-targeted praise was rated more pleasant than appearance-targeted praise. This effect was absent in women and consistent with men’s higher arousal ratings for personality- relative to appearance-targeted comments. Our findings suggest that men are more concerned about external perception of their personality than that of their appearance whereas women’s affective judgment is more balanced. These gender-specific results may have implications for topic selection in evaluative social communication.